Paleopathological and Molecular Study on Two Cases of Ancient Childhood Leprosy from the Roman and Byzantine Empires. (4th April 2012) - Rubini, Mauro; Erdal, Yilmaz S.; Spigelman, Mark; Zaio, Paola; Donoghue, Helen D.
ABSTRACT This study is based on the paleaopathology of leprosy on human skeletal remains and the detection of ancient Mycobacterium leprae DNA. Two cases of childhood leprosy were recognized. The first case was in a Roman necropolis at Martellona (Rome, Central Italy), dated to the 2nd to 3rd centuries ce. The skeleton of a child aged 4–5 years, from tomb 162, is the youngest individual in Italy from this time period, with the clear rhino‐maxillary syndrome and other bony changes indicative of leprosy. The second case from a burial at Kovuklukaya, in the Sinop region of Northern Turkey, was from the 8th to the 10th centuries, during the Byzantine era. The endocranium of a 4–5‐month‐old infant with new bone formation—an indication of chronic inflammation—was positive for M. leprae DNA. Infant and childhood leprosy is uncommon today, and there is a scarcity of information in the osteoarchaeological literature of leprosy in the past, especially in children. The significance of these cases is that it adds to an understanding of the history of the disease in the former Roman Empire. It is hoped that over time sufficient data can be obtained to understand the epidemiological dynamics and clinical evolution of leprosy from the ancient period until today. Copyright © 2012 John Wiley & Sons, Ltd.